Large web openings in steel and composite beams. Issue 2 (May 2017) - Lawson, R. Mark; Hanus, Francois; Sonck, Delphine
Abstract: This paper presents the basis for the design of steel and composite beams with large web openings. The main design requirements are the transfer of shear by Vierendeel bending and the control of web buckling next to and between the openings. Cellular beams with regular circular openings are a common example of highly perforated beams and their flange areas are often highly asymmetric. For these beams, web‐post moments may be generated to develop the full shear resistance of the cross‐section. Tests on beams with circular, elongated circular and rectangular openings are presented which are used to verify the design methodology. In addition, the openings cause local displacements due to shear and bending, which add to the overall deflection of perforated beams. Simplified formulae are presented to determine the additional deflection relative to the equivalent solid‐web beams.